Predicting Reading Performance by Texas Student Demographics Characteristics: A Statewide Analysis - Heather Hamilton; Frederick C. Lunenburg; John R. Slate; Wally Barnes (International Journal of Social Learning (IJSL), 2021)
Analyzed in this research study was the degree to which demographic characteristics (i.e., economic status, ethnicity/race, English Language Learner status) of Grade 3 students in Texas schools was related to their reading achievement as assessed by the State of Texas Assessment of Academic Readiness (STAAR) Reading test. Archival data from the Texas Education Agency, Public Education Information Management System, were analyzed using a causal-comparative research design. Specifically examined was each of the variables listed above for 2015-2016, 2016-2017, 2017-2018, and 2018-2019 school years separately for boys and girls, followed by comparing these variables across the four school years. Statistically significant results were present in all four school years for boys and girls. In three of the four years analyzed regarding boys' performance, being Poor, Black, or Hispanic was indicative of not meeting the Meets Grade Level standard. In three of the four years investigated regarding girls' performance, being White or Asian was indicative of meeting the Meets Grade Level standard. Implications for policy and practice, as well as recommendations for future research, are provided.